2017
DOI: 10.1016/j.urology.2016.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Belladonna and Opium Suppository for Ureteral Stent Pain: A Randomized, Double-blinded, Placebo-controlled Study

Abstract: OBJECTIVE To investigate whether the use of a belladonna and opium (B&O) rectal suppository administered immediately before ureteroscopy (URS) and stent placement could reduce stent-related discomfort. METHODS A randomized, double-blinded, placebo-controlled study was performed from August 2013 to December 2014. Seventy-one subjects were enrolled and randomized to receive a B&O (15 mg/30 mg) or a placebo suppository after induction of general anesthesia immediately before URS and stent placement. Baseline ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…23 Intraoperative use of nonopiate medications, such as intravenous toradol and belladonna opium suppositories have been shown to help with postoperative pain control after ureteroscopy. 11,24 Notably in this study, no surgical factors were identified as risk factors for persistent opiate use, including stent duration or sheath use. After surgery, providing a standardized MED per postoperative opiate prescription may help minimize the quantity of opiates prescribed and/or unused by patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…23 Intraoperative use of nonopiate medications, such as intravenous toradol and belladonna opium suppositories have been shown to help with postoperative pain control after ureteroscopy. 11,24 Notably in this study, no surgical factors were identified as risk factors for persistent opiate use, including stent duration or sheath use. After surgery, providing a standardized MED per postoperative opiate prescription may help minimize the quantity of opiates prescribed and/or unused by patients.…”
Section: Discussionmentioning
confidence: 76%
“…7,8,10 Specifically, unanticipated visits after ureteroscopy for stone disease has been reported to be 6.6%, and the majority of these visits are made due to pain. 5,11 An important finding of our study is that most patients before stone surgery have had opiate exposure within the previous 30 days, and a significant proportion have had multiple prescriptions. This highlights a fundamental challenge of addressing how and when opiates are prescribed to kidney stone patients as they often encounter multiple providers across different settings.…”
Section: Discussionmentioning
confidence: 82%
“…24,25 Other medical therapies include anticholinergic medication with solifenacin, preoperative belladonna and opium suppository, and periureteral botulinum toxin type A injection. [26][27][28] Incorporation of certain medical therapies to reduce stent discomfort should be considered part of routine postoperative care after URS. While we found a significant association between phone calls with stent extraction string and stent removal at home, others have reported no difference in stent-related quality of life, pain at stent removal, rates of UTI, ED visits, or phone calls.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the bladder mucosa normalised after the instillation. Table 4 provides a summary of existing studies about this issue, and most of the studies used the USSQ to measure the clinical discomfort caused by ureteric stenting [31][32][33][34][35][36][37][38][39][40][41]. As shown in Table 3, current existing evidence supports the specific treatment strategy to control discomfort due to ureteric stent indwelling either by a-blockers or other treatments.…”
Section: Discussionmentioning
confidence: 99%